Complexo Hub : coworking, cultura e comércio - Tognon, Danicléia (2022)
The HUB Complex is a project developed as a proposal for the final graduation work of the Architecture and Urbanism course at the University of Passo Fundo. It is a new space for the city of Tapejara, contemplating coworking, commerce, restaurant, sports, leisure and culture environments, where the aim is to accompany the economic development of the region in addition to bringing quality public spaces. The need arises from the demand for support buildings that meet the potential of the place, which currently has a high flow of people. The work also deals with design references to support the development of the project. The main objective of the proposal is to connect people with spaces and the way in which the project is linked to the city. Where, linked within this connectivity, they bring a contemporary space that works with innovation, sustainability and follows global trends, also prioritizing permeability and quality of life.